2012
DOI: 10.1007/s10616-012-9492-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the stem cell and non-stem cell constituents of human breast milk

Abstract: The immense potency of nutritional components of human breast milk and importance of breastfeeding is known worldwide. Recent researches had identified stem cells as integral component of human breast milk. Nevertheless, there is little proof of evidence on the stem cell constituents of breast milk. It is imperative to explore the cellular constituents of human breast milk, including of stem cells, to open new avenue in child's development and regeneration. Thus, we aimed at identifying the cellular constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 30 publications
(50 reference statements)
2
40
0
Order By: Relevance
“…Flow cytometry has provided insight to cellular breast milk composition and stem cells have been found in breast milk (5,12,13). Human breast milk contains heterogeneous populations of cells with high variability related to individual factors as well as the stage of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry has provided insight to cellular breast milk composition and stem cells have been found in breast milk (5,12,13). Human breast milk contains heterogeneous populations of cells with high variability related to individual factors as well as the stage of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In women infected with HIV-1 and HTLV-1, however, the activity of these cells unfortunately enables mother to infant viral transmission (see article by Lawrence in this issue). Stem cells have also been identified in human milk; 88,90 their function is under investigation.…”
Section: Immunological Factorsmentioning
confidence: 99%
“…It is noteworthy that CK18/CK14 double-positive cells can also be found in breast milk (F. Hassiotou, unpublished data), potentially suggesting the presence of progenitors (35) and highlighting the fact that care must be taken in interpreting tissue immunostaining and milk flow cytometry data, because the markers currently known to distinguish different mammary cell populations are not definitive. For example, Indumathi et al also reported the presence of myoepithelial cells in colostrum, but the markers used to identify these and other cell types were not myoepithelial cell-specific (36).…”
Section: The Cellular Composition Of Human Milkmentioning
confidence: 99%
“…In addition, preliminary investigations indicate the presence of CD34 + hematopoietic stem/progenitor cells in colostrum and breast milk (14,36), which almost certainly originate from the maternal bloodstream. The properties of these cells, the mechanisms of their transfer into breast milk, and their roles remain to be established.…”
Section: Breast Milk Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation